The Relationship between Exclusive Breastfeeding and Diarrhea in Under Six Months Infants in 2017 (Analysis of Indonesian Health Demography Data Survey 2017) - Fikriya Rusyda; Sudarto Ronoatmodjo (Jurnal Epidemiologi Kesehatan Komunitas, 2021)
Background: Diarrhea is the main cause of malnutrition in underfive children. One of the efforts to prevent diarrhea in infants is exclusive breastfeeding. Exclusive breastfeeding is infant that receives only breast milk without any additional consumption from 0 to 6 months. Under six months infant who are not exclusively breastfed have a higher risk of developing diarrhea than those who are exclusively breastfed.Methods: This study aims to determine the relationship between exclusive breastfeeding and the incidence of diarrhea in under six months infants in Indonesia. This study analyze secondary data from the 2017 Indonesian Demographic and Health Survey. The sample in this study consist of all live infants aged 0-6 months born to women aged 15-49 years in Indonesia who were successfully interviewed and had a complete answer (no answer missing). After weighting, 1898 samples were obtained.Result: The result found that the proportion of diarrhea incidence in Indonesia is 9.1%. Meanwhile of all infants, 36% were not exclusively breastfed. The results showed that there was a significant relationship between infants who were not exclusively breastfed and diarrhea incidence in Indonesia after adjusted by mother's education level, maternal employment status, mother’s economic level, area of residence, and latrine ownership (PR = 2.12, 95% CI = 1.46-3.07).Conclusion : Infants who were not exclusively breastfed increase the risk for diarrhea. Therefore it is necessary to have a program to increase the coverage of exclusive breastfeeding. The program can take the form of counseling by health workers in health services.